MODL-11. The tumor suppressor CREBBP and the oncogene MYCN cooperate to induce malignant brain tumors in mice. (3rd June 2022) - Melanie, Schoof; Epplen, Gefion Dorothea; Walter, Carolin; Ballast, Annika; Holdhof, Dörthe; Göbel, Carolin; Neyazi, Sina; Albert, Thomas; Kerl, Kornelius; Schüller, Ulrich
Abstract: CREBBP (cAMP response element-binding protein binding protein) and MYCN (v-myc avian myelocytomatosis viral oncogene neuroblastoma derived homolog), two essential proteins in central nervous system development that are described to be genetically altered in the same brain tumor entities, such as high grade glioma or medulloblastoma. Therefore, we hypothesized that alterations in both genes cooperate to induce brain tumor formation. In order to investigate molecular mechanisms and potential tumor formation, we established a novel mouse model combining a deletion of Crebbp with an overexpression of MYCN in neural stem cells ( hGFAP-cre::CrebbpFl/Fl::lsl-MYCN ). The animals developed highly aggressive forebrain tumors with 75 % penetrance already detectable in seven-day old mice, leading to tumor-related death within eight months. Although tumors mostly developed in the olfactory bulb region, we hypothesized that these tumors develop from subventricular stem cells that migrate into the olfactory bulb, where they settle and establish large solid tumors. In order to test this hypothesis, we analyzed neural stem cells (NSCs) derived from our mouse model. Compared to control cells, NSCs from transgenic mice have a significantly increased cell viability and proliferation in vitro and did not undergo full glial differentiation. In order to gain further insights into the cellular origin and biology of the tumors, we finally employed single cell RNA sequencing. Apart from a high intratumoral heterogeneity within the tumor cell population, data comparison with non-neoplastic CNS cell populations revealed a high similarity with transit-amplifying NSCs of the subventricular zone. Together, we were able to show the oncogenic potential of a combined loss of Crebbp and aberrant expression of MYCN in neural stem cells. This novel mouse model will be an important tool for understanding tumor-driving mechanisms and a valuable model for preclinical testing and will thereby help to improve patient care.